Accessing 1, 8‐Naphthyridones by Metal‐Free Regioselective Amination of Pyridine N‐oxides/Acid‐Mediated Cyclization. Issue 18 (24th August 2020) - Zhao, Lianbo; Hao, Lei; Fu, Yupeng; Cheng, Yan; Pan, Guojun; Désaubry, Laurent; Yu, Peng; Wang, Dong
Abstract: A concise and practical method for the metal‐free synthesis of 1, 8‐naphthyridones is described using a two‐step approach involving regioselective amination of pyridine N ‐oxides and acid‐mediated cyclization. This is the first synthesis of 1, 8‐naphthyridones utilizing easily accessible pyridine N ‐oxides as substrates. Compared to previous reports, this method benefits from simple operation, easy access to starting materials, and a wide substrate scope, providing a variety of novel 1, 8‐naphthyridones. Abstract :